Ultrasonic control of aquatic macrophytes in reservoirs: An integrated review (Research, Society and Development, 2024)
The excessive proliferation of cyanobacteria and aquatic macrophytes in water reservoirs has been a concern for governments, energy companies managing hydroelectric and thermal power plants, and local populations. These aquatic organisms, when overabundant, negatively impact the management of water for public supply and energy generation, obstructing intake systems and damaging water treatment stations. Ultrasound emerges as a potential technique for controlling these organisms. The aim of this study was to perform an integrative review by selecting articles published between 2020 and 2024, focusing on the efficacy and ecological implications of ultrasonic control on these aquatic populations. The methodology involved searching scientific databases, selecting 14 articles out of a total of 42, based on their relevance to the theme of ultrasonic control and its practical applicability. The results indicate that ultrasonic frequencies of 20 kHz collapsed gas vacuoles in these aquatic organisms within 40 seconds of exposure, demonstrating the potential application of this technique in controlling these organisms, although it is necessary to adjust the intensity according to the specific environmental conditions of the reservoir and the biology of the target organisms. However, exposure to ultrasound can release toxins, affect non-target organisms, and alter the aquatic community structure, resulting in negative impacts such as hypoxia and fish death. It highlights the need to adopt an adaptive model to adjust ultrasound parameters and integrate them with other management practices. The study emphasizes the importance of conducting laboratory-scale tests and continuous monitoring to optimize efficacy and minimize environmental risks. Future development of more efficient and less invasive ultrasonic transducers is also recommended, as well as interdisciplinary collaboration to promote more sustainable reservoir management.